Modelos de negocios en pymes agroindustriales: desafíos en el siglo XXI (2018)
Through a detailed study, the search and analysis of information was carried out from the perspective of the agro-industrial activity of small and medium enterprises in the current economic context, the importance of the development of human talent skills, changes of attitude in a competitive environment and the various challenges faced by small and medium-sized enterprises (SMEs) in the areas of innovation, strategic planning, entrepreneurship, and new business opportunities.It is also important to know which are the topics of greatest interest to the scientific community through a specific software, which has the capacity to identify research trends with respect to the competitiveness of companies and the importance of adapting new business models for small and medium (SMEs) agro-industrial companies. It does this through tools and strategies that increase the efficiency of processes and frame new dynamic ventures with sustainable potential.It was concluded that there is a marked trend in research with information regarding the competitiveness of small and medium- sized companies in Ibero-American territories from 1998 to 2013. Nationally, some factors are lacking in the organizational structure of agro-industrial SMEs and in recent years, there is a greater exchange of foreign currency for import of agricultural products in relation to products exported from Colombia.